Glossary on agricultural landscapes - Kruse, Alexandra; Centeri, Csaba; Renes, Hans; Roth, Michael; Printsmann, Anu; Palang, Hannes; Benito Jordá, Lucia; Velarde, Maria Dolores; Kruckenberg, Helmut (JOURNAL OF LANDSCAPE ECOLOGY, 2010)
The following glossary of terms related to the European agricultural landscape shall serve as a common basis for all parties, working in or on agricultural landscapes. Some of the terms are quite common and sometimes used in our every day language, but they often have different meanings in particular countries. These differences may be a result of varying linguistic developments, history and traditions. The glossary contains 40 terms in seven languages; English, Dutch, Estonian, French, German, Hungarian, and Spanish. Each term begins with an English definition, illustrated by a photograph. If there are differences in meanings and connotations of single countries, they are mentioned in the designated country’s column. This work is to be continued.
Keywords: glossary; agricultural landscapes; policy; planning; landscape